Mainstreaming Inclusive Narratives and Content in Digital Media in the Face of the 2024 Elections - Ali Ridho; Wahyu Ilaihi; Muhammed Sharin Haji Masri; Arinil Haq; Abdul Mana Nasution (Jurnal Dakwah dan Komunikasi, 2024)
This article uses a qualitative type of virtual ethnography method and literature review in obtaining the main data derived from the results of searching, collecting, and processing fifty reputable national and international scientific journals, general and religious-based online news websites, and social media platforms. Indonesian society has lived together in a socio-religious context with an atmosphere of peace, tolerance in the frame of diversity, and prioritizing the values of religiosity. However, this peace and harmony has turned into conflict, hostility and discrimination triggered by political elites using religion through identity politics and politicization of religion to gain power in elections. The conclusion of this research is that there must be a series of strategies by the government, religious leaders, and plural communities in moderating the digital world and cross-cultural religious literacy based on digitalization in the form of massive and inclusive positive content. Echoing the political narrative of humanity which is the spirit of politics, until finally a soothing social and digital media climate is created without any negative tendencies that become seeds of discrimination and conflict when elections come.